Effect of photoperiod regimes on the cultivation of Nannochloropsis sp. in palm oil mill effluent for lipid production - Karthiani, Kanagesan; Palanisamy, Karthick Murugan; Rameshprabu, Ramaraj; Mohd Hasbi, Ab Rahim; Govindan, Natanamurugaraj; Maniam, Gaanty Pragas (Universiti Putra Malaysia, 2021)
Microalgae require a photoperiod (light:dark) regime for effective photosynthesis. Photoperiod regimes affect the development and metabolic processes of microalgae. The purpose of this research was to investigate the impacts of continuous illumination vs. photoperiod conditions on growth and biomass content in Nannochloropsis sp., with an emphasis on bioactive components such as lipids. The impacts of photoperiod regimes on the development of Nannochloropsis sp. were investigated to maximize microalgal output in massive culture systems and lipid content. Nannochloropsis sp. was grown aseptically in 10% POME for 14 days under four different photoperiod regimes (24:00, 18:06, 12:12, and 06:08 h light:dark). The findings revealed that varying photoperiods had a significant impact on Nannochloropsis sp. growth and lipid accumulation. Nannochloropsis sp. showed improved cell growth under 18:06 h light: dark after 14 days of flask cultivation, with a highest dry biomass of 0.712 g L-1 and recovered 29.5% lipid. By altering the photoperiod, this work shows an alternative strategy to stimulate development and intracellular lipid accumulation of Nannochloropsis sp.